Differences in cardiorespiratory responses to upper and lower extremity exercise - Chickonoski, T. (1997)
This assignment will discuss the various components resulting in cardiorespiratory response to upper and lower extremity exercise. A review of cardiac and pulmonary responses to exercise will be discussed. Examination of blood pressure, heart rate, venous return, cardiac output, maximum oxygen consumption, sympathetic and central neural control will be discussed regarding upper and lower extremity exercise. Finally, the clinical implications regarding exercise prescription will be reviewed and our responsibilities as sports physiotherapists in organising training programs will be discussed.